Formation of emotional intelligence of students in biochemistry classes by means of dialogical learning - Чувасова, Н. О. (Pedagogy of Higher and Secondary Education, 2011)
The article deals with the necessary of formation of the would-be teachers’ emotional intelligence at a higher educational institution. Also some ways and methods of the solution of the problem of formation of emotional intelligence in the course of studying biochemistry are considered.